Complex transitions between dihydrate and anhydrate forms of ectoine – unexpected behavior of a highly hygroscopic compatible solute in the solid state. Issue 2 (4th December 2019) - Hützler, Wilhelm Maximilian; Mossou, Estelle; Vollrath, Ronnald; Kohagen, Miriam; El Ghrissi, Imadine; Grininger, Martin; Zaccai, Giuseppe; Smiatek, Jens; Oesterhelt, Dieter
Abstract : Crystallizing the compatible solute ectoine from water yields a metastable dihydrate that readily degrades to a highly hygroscopic anhydrate at ambient conditions; this strange behavior is examined and a rationale is presented. Abstract : The crystalline dihydrate of the compatible solute ectoine undergoes a loss of water at ambient conditions and transforms into a highly hygroscopic anhydrate form. This unexpected transition is studied combining single-crystal and powder X-ray, single crystal neutron diffraction measurements and quantum mechanical calculations. Overall, our study provides a rationale for the important uptake and loss of water by ectoine in the solid state.